Contribution of Local Food to Meeting Needs Staple Food in Farmer Households in Laiba Village Parigi Sub-district, Muna Regency - Adel Listiani; Saediman, Saediman; Sitti Aida Adha Taridala (International journal of technology and education research, 2025)
This research aims to determine and analyze the contribution of local food to meeting the basic food needs of farming households in Laiba Village, Parigi District, Muna Regency. Furthermore, this research also analyzes the factors that influence local food consumption in farming households. The food commodities included in the model include three commodities including: rice, corn and cassava. The method used in this research is a quantitative descriptive analysis method and the Almost Ideal Demand System (AIDS) model equation which is estimated using the R-Studio method. The results of this research show that 1) The contribution of corn and cassava in providing food for farming households is still small compared to rice, where corn is only consumed on average 1.0 days a week, and no one consumes cassava as a staple food. Rice is consumed on average 6.0 days a week. Corn is now the second staple food after rice, while cassava is only consumed as a snack or snack for farming households, and 2) Factors that have a real (significant) influence on corn consumption are family income and number of family members, while the demand for cassava and rice is influenced significantly by the number of family members.